Constraints in The Implementation of Problem-Based Learning in Subject of History in State Senior High School 2 Sendawar - Petronela Sherlly; Jamil Jamil; Muhamad Sopyan (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2018)
This study aims to determine the application of historical learning model by using problem-based learning and obstacles from implementing problem-based learning model in history learning. This research uses descriptive qualitative research method. Data collection using observation and interview techniques. The result of the research shows that learning process is more centred on student activity with problem-solving related to history lesson material and obstacles in applying problem-based learning is the understanding and ability of educator in using learning model, complicated, limited time, facilities and infrastructure.